PERFORMANCE OF PRIMARY HEALTH CENTRES: A STUDY WITH REFERENCE TO VADAKARA PHC - Vayalambron, Lijina (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Health is an important part of human resources development. For creating healthy citizens in a society authorities should provide essential health care facilities and services. The essential step for provision of good health care is active working of the primary health centers. Primary health centres are designed for combined curative and preventive health needs of the rural people. Services of Primary health centers are availed by the people of all ages. The services included provision of vitamin tablets, iron tablets for pregnant woman, testing blood pressure, diabetics, vitamin deficiencies and immunization for infant and citizen. Additional physicians, health assistants and infrastructures facilities are vital in the primary health center in order to minimize the gap between supply and demand for health care. Access to health services, provision of essential medicine and security doctors are other bottlenecks in the primary health care scenario. Government should promote health care programs for deprived sections along with mass immunization and fertility control measures through primary health centers.